First Report of Broad bean wilt virus 2 in Leonurus sibiricus in Korea - Seo, J-K (Plant disease, 2014)
Leonurus sibiricus L. (family Lamiaceae) has been used as a traditional herbal remedy to treat various gynecologic diseases. Although it is a widely distributed subtropical weed in Southeast Asia, L. sibiricus have been commercially cultivated on a small scale in many geographic areas of Korea. In August 2012, field-grown L. sibiricus plants showing mosaic, yellowing, and stunting symptoms were collected near a pepper field in Andong, Korea. Since L. sibiricus is only consumed as a raw material of traditional medicine in Korea, symptomatic plants lose commercial value entirely. To identify the causal agent(s) of the virus-like symptoms, total RNA was extracted from the symptomatic leaves, and a transcriptome library was generated using the TruSeq Stranded Total RNA with Ribo-Zero plant kit (Illumina, San Diego, CA) according to the standard protocol. Next-generation sequencing (NGS) was performed using an Illumina HiSeq2000 sequencer. De novo assembly of the quality filtered NGS reads (101-bp paired-end reads) were performed using the Trinity pipeline and the assembled contigs (92,329 contigs) were analyzed against the viral reference genome database in GenBank by BLASTn and BLASTx searches (3). The entire NGS procedure was performed by Macrogen Inc. (Seoul, South Korea). Among the analyzed contigs, only two large contigs were clearly of viral origin. Nucleotide blast searches showed that the first and second contigs (5,914 and 3,534 bp, respectively) have maximum identities of 91 and 95% to RNA1 of the isolate RP3 (GenBank Accession No. JX183225) and RNA2 of the isolate RP7 (JX183234) of Broad bean wilt virus 2 (BBWV-2), which were isolated from pepper in Korea. The NGS results were confirmed by analyzing the sequences of the fragments covering the entire BBWV-2 genome amplified by RT-PCR using specific primers for BBWV-2 as described previously (1). To obtain the complete genome sequence, terminal sequences of both RNA segments were analyzed by the 5' and 3' rapid amplification of cDNA ends (RACE) method as described previously (1). The assembled full-length sequences of BBWV-2 RNA1 and RNA2 isolated from L. sibiricus were 5,951 and 3,575 nucleotides in length, respectively, and deposited in GenBank under the accessions KM076648 and KM076649, respectively. BBWV-2 belongs to the genus Fabavirus in the family Secoviridae and it is known to have a wide host range. To investigate the host range of the BBWV-2 isolated from L. sibiricus, sap from the symptomatic leaves of L. sibiricus was inoculated to the test plants including Nicotiana benthamiana, Capsicum annuum (red pepper), and C. annuum var. gulosum (Paprika). RT-PCR detection and sequencing of the amplicons showed that all the inoculated test plants were infected with the BBWV-2 isolated from L. sibiricus. Currently, BBWV-2 is epidemic in pepper fields in Korea (1,2). Because BBWV-2 is easily transmitted by various aphids, and L. sibiricus is widely distributed in both wild and cultivated fields in Korea, this host might serve as a potential source of BBWV-2 to other crops such as pepper. To the best of our knowledge, this is the first report of BBWV-2 in L. sibiricus. References: (1) H.-R. Kwak et al. Plant Pathol. J. 29:274, 2013. (2) H.-R. Kwak et al. Plant Pathol. J. 29:397, 2013. (3) S.-E. Schelhorn et al. PLoS Comput. Biol. 9:e1003228, 2013